Transmission potential and severity of COVID-19 in South Korea - Shim, Eunha; Tariq, Amna; Choi, Wongyeong; Lee, Yiseul; Chowell, Gerardo (International journal of infectious diseases, 2020)
•COVID-19 caused 6284 cases and 42 deaths in South Korea as of March 6, 2020.•The mean reproduction number Rt of COVID-19 in Korea was estimated at 1.5.•The crude case fatality rate is higher among males and increases with age.•Sustained disease transmission of COVID-19 in the region is suggested.•Our estimates support the implementation of social distancing measures in Korea. Since the first case of 2019 novel coronavirus (COVID-19) identified on Jan 20, 2020, in South Korea, the number of cases rapidly increased, resulting in 6284 cases including 42 deaths as of Mar 6, 2020. To examine the growth rate of the outbreak, we present the first study to report the reproduction number of COVID-19 in South Korea. The daily confirmed cases of COVID-19 in South Korea were extracted from publicly available sources. By using the empirical reporting delay distribution and simulating the generalized growth model, we estimated the effective reproduction number based on the discretized probability distribution of the generation interval. We identified four major clusters and estimated the reproduction number at 1.5 (95% CI: 1.4–1.6). In addition, the intrinsic growth rate was estimated at 0.6 (95% CI: 0.6, 0.7), and the scaling of growth parameter was estimated at 0.8 (95% CI: 0.7, 0.8), indicating sub-exponential growth dynamics of COVID-19. The crude case fatality rate is higher among males (1.1%) compared to females (0.4%) and increases with older age. Our results indicate an early sustained transmission of COVID-19 in South Korea and support the implementation of social distancing measures to rapidly control the outbreak.